Multi-objective optimization of a pressurized solid oxide fuel cell – gas turbine hybrid system integrated with seawater reverse osmosis. (15th March 2017) - Eveloy, Valerie; Rodgers, Peter; Al Alili, Ali
Abstract: To improve the capacity and efficiency of distributed power and fresh water generation in coastal industrial facilities affected by regional water scarcity, a natural gas-fueled, pressurized solid oxide fuel cell-gas turbine (SOFC-GT) hybrid is integrated with a bottoming organic Rankine cycle (ORC) and seawater reverse osmosis (RO) desalination plant. This power and water co-generation system is optimized in terms of two objectives, maximum exergy efficiency and minimum cost rate, using a genetic algorithm. The exergetic and economic performance of three solutions representing maximum exergy efficiency, minimum cost rate, and a compromise between efficiency and cost rate, are compared. When imposing a water production requirement (reference case), the selected compromise multi-objective optimization solution delivers a net power output of 2.4 MWe and 636 m 3 /day of permeate, at a co-generation exergy efficiency and cost rate of 71.3% and 0.0256 USD/s, respectively. The system payback time is estimated to be less than six years for typical economic parameters, but would become unprofitable in the most unfavorable economic scenario considered. Overall, the results indicate the thermodynamic and economic benefits of reverse osmosis over thermal desalination processes for integration with high-efficiency power generation systems in coastal regions impacted by domestic gas shortages and water scarcity. Highlights: Integration of a pressurized SOFC-GT hybrid system with a reverse osmosis unit. Multi-objective, exergetic and economic optimization using a genetic algorithm. Optimum solution delivers 2.4 MWe and 636 m 3 /day of desalinated water. Overall exergy efficiency and cost rate of 71.3% and 0.0256 USD/s, respectively. System payback time estimated at less than six years for typical economic conditions.